Efecto de una pasta a base de propóleo para el tratamiento de gingivitis en perros domésticos en el barrio la magdalena parroquia Machachi cantón, Mejía provincia de Pichincha - Chiguano Jarrin, Diego Armando (2015)
The research was conducted in La Magdalena Neighborhood, Machachi Parish, Mejía Town, Pichincha Province, which lasted 15 days. The objective was to evaluate the effect a paste of propolis for treatment from gingivitis in domestic dogs, The study consists of two treatments: Treatment one (Application of a paste of commercial use "ORLY") cleaning is performed every forty eigth hours as directed by the commercial house, Treatment two (Apply a paste of propolis) two cleaning daily applied every twelve hours and while exhibiting changes were evaluated by bacterial counts in buccal mucosa swab (UFC/ml), at the end of the application with the 2 treatments, it was used Student-t technique with which it could be used determine that the variances don’t show significant differences, Since the statistical T = 0,622 therefore lower than the critical value and that the statistical probability of 0.5490 is greater than 0.05, therefore the 2 treatments were found to be effective for treating canine gingivitis in different degrees of manifestation, the effectiveness of propolis is related to its concentration either pure or in this excerpt, since within its many properties is anesthetic, anti-inflammatory, antibacterial, fungicide and adjuvant solution with which you are working….